Analisis tingkat produktivitas industri manufaktur di Indonesia periode 1990-1998 - Vincent Gaspersz (Economic Journal of Emerging Markets, 2001)
This research used a data collection through a document study which is relevant with the research problem. The data about manufacture industry that becomes the research object were got from BPS. Based on the empirical analysis, the researcher found (1) the total productivity of employees on manufacture industry faces a negative growth, on average of 0.23 percent per year during 1990-1998.